Spondyloarthritis: How far are we from precision medicine? - So, Jacqueline; De Craemer, Ann-Sophie; Elewaut, Dirk; Tam, Lai-Shan (Frontiers in Medicine, 2022)
Spondyloarthritis (SpA) is a family of heterogenous diseases consisting of different phenotypes. The exact disease mechanism remains unclear but evidence shows the complex pathophysiology with interplay between genome, microbiome and immunome. Biologic DMARDs have markedly improved patients’ disease control and quality of life. However, treatment response varies among patients. There is a growing need to identify biomarkers for the diagnosis, prognosis, prevention, and treatment of SpA. Genomic studies have been the research focus in the past two decades and have identified important genes involved in SpA. In recent years, emerging evidence supports the link between gut and joint inflammation in SpA, in which the role of gut microbiome in SpA is of great interest. Herein, potential genetic and gut microbial biomarkers for predicting treatment response are discussed. Novel strategies targeting dysbiosis in SpA are also summarized. These results represent a significant step towards precision medicine for patients with SpA.